Update on cardiovascular prevention in clinical practice: A position paper of the European Association of Preventive Cardiology of the European Society of Cardiology. (29th August 2020) - Piepoli, Massimo F; Abreu, Ana; Albus, Christian; Ambrosetti, Marco; Brotons, Carlos; Catapano, Alberico L; Corra, Ugo; Cosyns, Bernard; Deaton, Christi; Graham, Ian; Hoes, Arno; Lochen, Maja-Lisa; et al.
Abstract: European guidelines on cardiovascular prevention in clinical practice were first published in 1994 and have been regularly updated, most recently in 2016, by the Sixth European Joint Task Force. Given the amount of new information that has become available since then, components from the task force and experts from the European Association of Preventive Cardiology of the European Society of Cardiology were invited to provide a summary and critical review of the most important new studies and evidence since the latest guidelines were published. The structure of the document follows that of the previous document and has six parts: Introduction (epidemiology and cost effectiveness); Cardiovascular risk; How to intervene at the population level; How to intervene at the individual level; Disease-specific interventions; and Settings: where to intervene? In fact, in keeping with the guidelines, greater emphasis has been put on a population-based approach and on disease-specific interventions, avoiding re-interpretation of information already and previously considered. Finally, the presence of several gaps in the knowledge is highlighted.